1992
DOI: 10.1115/1.2929183
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence Modeling for Secondary Flow Prediction in a Turbine Cascade

Abstract: Predictions of secondary flow in an axial turbine cascade have been made using three different turbulence models: mixing length, a one-equation model and a k–ε mixing length hybrid model. The results are compared with results from detailed measurements, not only by looking at mean flow velocities and total pressure loss, but also by assessing how well turbulence quantities are predicted. It is found that the turbulence model can have a big influence on the mean flow results, with the mixing length model giving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…As above, the magnitude of the secondary kinetic energy is over predicted suggesting that the secondary velocities generated within the blade passage are being dissipated too slowly by the turbulence model. This has been observed by other researchers (eg Cleak and Gregory-Smith, 1992)Hartland et al (2000) for the evaluation of their contoured endwall relative to the planar configuration.The simulations ofHartland et al (2000) used a structured grid topology and an algebraic mixing length turbulence model with a wall function.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…As above, the magnitude of the secondary kinetic energy is over predicted suggesting that the secondary velocities generated within the blade passage are being dissipated too slowly by the turbulence model. This has been observed by other researchers (eg Cleak and Gregory-Smith, 1992)Hartland et al (2000) for the evaluation of their contoured endwall relative to the planar configuration.The simulations ofHartland et al (2000) used a structured grid topology and an algebraic mixing length turbulence model with a wall function.…”
supporting
confidence: 79%
“…Hildebrand and Fottner (1999) showed higher predicted losses in the two dimensional wake and secondary flow using both the k -e and k -u turbulence closure models. Cleak and Gregory-Smith (1992) Hildebrand and Fottner (1999) and Cleak and Gregory-Smith (1992), the over prediction of secondary loss can be partially accounted for by the assumption of a fully turbulent boundary layer on the endwall of the blade passage. It is unclear why the computations of Hjarne et al (2007) under predict the loss without the implementation of a transition model.…”
Section: Flow Visualizationmentioning
confidence: 99%
“…The kε turbulence models are appropriate for flows characterized by high adverse pressure and intensive separation. This model allows for a more accurate near wall treatment with an automatic switch from wall function to low-Reynolds number formulation, based on grid spacing see [125][126][127][128].…”
Section: An Example Of Modeling Of Turbine Stage With Twisted Rotor Bmentioning
confidence: 99%
“…cores and in the blade wake. While the difference might be partially due to limited spatial resolution in the experiment, it has also been shown that eddy-viscosity turbulence models tend to overpredict both secondary and midspan blade wake losses ( [31]). The flat endwall predictions using the realizable k-ε turbulence model (Figure 7c) show poor agreement for both C SKE and C Ptot when compared to the measurements in Figure 7a.…”
Section: Table 3 Ideal Blowing Ratios and Flowratesmentioning
confidence: 99%